Antibacterical Activity Test of Suji Leaf Fraction (Dracaena angustifolis (Medik.) Roxb) against the Growth of Staphylococcus Epidermidis Acne-Causing Bacteria - Erika Wuryaningsih; Endah Widhihastuti (Universitas Negeri Semarang, 2024)
The suji plants is a plant that has benefits as an antibacterial, one of which is the leaves. Suji leaves contain chemical compounds such as flavonoids, alkaloids, saponins, steroids, terpenoids, and tannins. The compounds can function as antibacterials. The study aims to determine the value of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of suji leaf fractions against Streptococcus epidermidis bacteria. The antibacterial test method used is liquid dilution and solid dilution. The results obtained were the most active fraction that was able to inhibit Staphylococcus epidermidis was the n-hexane fraction with a KHM value of 6.25% and KBM 12.5%. The results obtained show that the N-Hexane fraction of suji leaves which is the most active fraction in inhibiting bacterial growth is not as good as clindamycin and ethanol extract in inhibiting Staphylococcus epidermidis bacteria, where ethanol extract has a KBM value of 6.25%. Meanwhile, clindamycin which is a positive control has been able to inhibit and kill the growth of Staphylococcus epidermidis bacteria at a concentration of 0.1%. The results of KBM values obtained from the most active samples are ethanol extract > n-hexane fraction > ethyl acetate fraction > ethyl acetate insoluble fraction. Bioautography KLT results show that the compounds responsible for antibacterial activity are thought to be flavonoids, steroids, and triterpenoids.